OPERATOR MESIN SENSO DI DESA SENDUK KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Ondang, Victor A. S. (HOLISTIK, Journal Of Social and Culture, 2016)
Man must adapt in order to survive, most elements of the culture that trail shows the adaptation between humans and their environment is their livelihood. Humans need jobs in the hold of life, a lot of work that can be occupied them with private workers or as a government employee. Everything is based on one's ability to adapt to its environment. For people who live around the forest will adapt to their environment and generate jobs in the utilization of forest products. The same thing happened on a number of people in the village Senduk, they prefer to work in the field of utilization of forest resources. Attempts to exploit forest resources mebuka jobs in some fields such as energy loggers or operator Chainsaw (Senso). Work as operator senso has dynamics of its own because this work is not occupied by many people. The reason why chooses to work as an operator becomes interesting to study and used as a scientific paper to answer questions about why they chose the community as a work operator senso and senso operator activity. Keywords: activity, carrier, senso